Relationship of Central Post-Stroke Pain with Location and Type of Lesions in Brain among Thalamic Stroke Patients (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Central post-stroke pain (CPSP) is a neuralgic pain syndrome following a stroke in thalamic region.Objective: The purpose of the present study was to see the relationship of Central Post-Stroke Pain with Location and Type of Lesions in Brain among Thalamic Stroke Patients.Methodology: This analytical cross-sectional study was carried out in the Department of Neurology at Dhaka Medical College and Hospital, Dhaka, Bangladesh during July 2013 to June 2015 for a period of two years. Patients with CPSP and without CPSP with isolated thalamic stroke within one year of event who were communicable with sufficient cognitive function were selected as study population. Demographic variables and clinical features were recorded by face to face interview, examination and by evaluating medical records. Pain perception was tested with the use of pinprick; temperature sense was tested with a cold tuning fork. Intensity of pain was graded on visual analogue scale (VAS).Results: This study was included 100 patients of which 50 cases were with CPSP and 50 cases were without CPSP. The mean age with SD of the study population were 57.2±11.4 years. 46% female, with isolated thalamic stroke. There was no significant difference between CPSP and non-CPSP groups in relation to age (p>0.05), gender ((p>0.05), area of living (p>0.05) or frequency of risk factors (p>0.05). Frequency of participants with impairment of pain and thermal sensation as well as allodynia and dysesthesia were significantly higher in CPSP group in comparison to those in non-CPSP group (p